Routine medical and dental examinations: a case study of adults in Tema community 20 in Ghana. Issue 6 (1st November 2020) - Danquah, Esther Priscilla Biamah; Agyemang, Samuel Agyei; Amon, Samuel; Aikins, Moses
ABSTRACT: Routine medical and dental examinations are important and effective measures in the prevention of diseases and promotion of good health. A cross-sectional quantitative study was conducted among adult residents in Community 20, Tema. The study randomly sampled 216 adults aged over 18 years. These participants were interviewed after informed consent was obtained. Socio-demographic factors associated with routine medical and dental examinations were determined using multivariable logistic regression analysis. Weighted mean was used to determine the level of perceived importance of medical and dental examination. A total of 68.1% and 31.9% of the adults have ever undergone routine medical and dental examination, respectively. Personal reasons constituted 35.4% for medical examination and 55.1% for dental examination. Medical and dental examinations encourage adults to be health conscious was ranked highest with a weighted mean of 3.78. Routine medical and dental examinations were higher among adults over 50 years, males, higher educated adults, higher income earners and the unmarried. Most of the adults indicated that medical and dental examinations were very important. Routine medical and dental examinations encourage adults to be health conscious. Routine medical and dental examinations were higher among adults over 50 years. Public health education programs should educate and encourage the general public especially among the younger population to undergo routine medical and dental examinations annually.